Efektivitas Media Dekak-Dekak Pada Operasi Penjumlahan 1-10 Bagi Siswa Tunagrahita Ringan Kelas 1 SLB-YPAC Kota Malang - Neny Yuniarti; Yohanes Subasno (Jurnal Pelayanan Pastoral, 2020)
Students with intellectual disabilities have limited thinking, especifically in abstract. That is the main factor causing the low learning achievement specifically in the field of arithmetic (mathematics). The selection of learning media that is suitable for the characteristics of intellectual disabilities is very important to bridge the abstract and concrete so that it is easy to understand. Media “dekak-dekak” becomes one of the learning media that is used in the sum operations for student with intellectual disability. The purpose of this study is to measure the effectiveness of the use of media “dekak-dekak” in the sum operation 1-10 for mild intellectual disability students in the 1st grade of Special School. This research is a class action research, which limits effectiveness based on the completeness minimum criteria (KKM) of 75 value points. A student, class teacher, and an observer participated in this study. The results of the study recorded the value of 50 points in the pre-cycle, the value of 70 points in the first cycle, and the value of 80 points in the second cycle. Thus, the media "dekak-dekak" effectively to be applied to the learning of the sum operations 1-10 for students with mild intellectual disabilities.